Assessing Intangible Assets and the Decrease in Earnings Clarity: A Review of Literature on the Impact of Mismatching - Ngadi Permana; Amelia, Yessica; Qalbia, Farah (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review examines the relationship between accounting for intangible assets, mismatching issues, and the declining informativeness of earnings. The findings reveal that traditional accounting frameworks inadequately address the growing significance of intangible assets, resulting in mismatching between revenues and expenses. Conservative accounting practices further exacerbate this issue by deferring the recognition of intangible-related expenditures, reducing the relevance of earnings as a decision-making tool. The review synthesizes insights from recent studies, highlighting the need for accounting reforms, such as the capitalization of certain intangible investments, to improve financial reporting accuracy. Furthermore, alternative metrics like adjusted earnings and advanced valuation models are discussed as potential solutions for mitigating mismatching effects. This study underscores the importance of evolving accounting standards to better reflect the economic realities of intangible asset-driven businesses.